2001
DOI: 10.1089/109662001753165756
|View full text |Cite
|
Sign up to set email alerts
|

Estrogenic Effects of Cimicifuga racemosa (Black Cohosh) in Mice and on Estrogen Receptors in MCF-7 Cells

Abstract: The estrogenic effects of Cimicifuga racemosa or Actacea racemosa (black cohosh, CR) extracts were tested in mice, and their effects on estrogen receptor (ER) levels in human breast cancer MCF-7 cells were also investigated. Four groups of weanling female Kunming mice were given 0 (control), 75, 150, or 300 mg/kg body weight CR extracts orally for 14 days. The estrus cycle and the weights of the uterus and ovary of mice, as well as serum estradiol (E(2)) were measured. The proliferation patterns of MCF-7 cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 19 publications
(19 reference statements)
0
12
0
Order By: Relevance
“…21 While many phytoestrogens have proestrogenic properties, and bind the ER with a similar affinity as 17b-estradiol itself, 22 black cohosh may have antiestrogenic effects that inhibit breast carcinogenesis. Black cohosh has been inferred to be antiestrogenic by studies that show a lack of estrogen-induced proliferation of breast cancer cells, 14,15,[23][24][25] showed no competitive binding to ERs nor regulation of estrogeninducible genes, 7 and protected against cellular DNA damage caused by reactive oxygen species by acting as an antioxidant. 26 These data are consistent with the hypothesis that black cohosh may be associated with protection from breast cancer risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…21 While many phytoestrogens have proestrogenic properties, and bind the ER with a similar affinity as 17b-estradiol itself, 22 black cohosh may have antiestrogenic effects that inhibit breast carcinogenesis. Black cohosh has been inferred to be antiestrogenic by studies that show a lack of estrogen-induced proliferation of breast cancer cells, 14,15,[23][24][25] showed no competitive binding to ERs nor regulation of estrogeninducible genes, 7 and protected against cellular DNA damage caused by reactive oxygen species by acting as an antioxidant. 26 These data are consistent with the hypothesis that black cohosh may be associated with protection from breast cancer risk.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not clear that use of black cohosh or Remifemin would necessarily be associated with the hormonal status of the tumors. Black cohosh has hormonal effects, but its action in terms of breast cancer risk may also be related to its antiproliferative properties, [4][5][6][7][8] which may or may not be independent of hormone receptor status or other hormonal hallmarks of the tumor. Furthermore, it is possible that most breast tumors become estrogen/progesterone sensitive and lose these receptors at a later stage in tumorigenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be speculated that ZEA, due to its oestrogen-like activity inhibits apoptotic processes in the ovary of intoxicated gilts. This effect might be compared to the action of phytoestrogens from soybean, or Cimicifuga racemosa (Wuttke et al, 2003), showing positive effect in postmenopausal women (Liu et al, 2001). However, it would be not wise to attribute all effects of ZEA to its oestrogenlike activity.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] However, one study found evidence of estrogenic activity in the urogenital tract of mice. [29] Recent data, in fact, has demonstrated that black cohosh acts on serotonin receptors which may be the mechanism for relief of hot flashes and improvement in mood. [30,31] Much of the research on black cohosh has been conducted in Germany since the 1940's.…”
Section: Black Cohosh (Cimicifuga Racemosa)mentioning
confidence: 99%